Influência da quantidade de leite desnatado sobre o desempenho de bezerros de três raças leiteiras - Mattoso, Joaquim; Américo Garcia, José (Revista Ceres, 2025)
Fifty-four Holstein crosbred calves were randomly assigned to either of three treatments which were balanced by sex with 9 males and 9 females per treatment. Also assigned in the same manner were 24 Guernsey crosbred calves and 24 Jersey crosbred calves, 8 of eachbreed per treatment and balance by sex with 4 males and 4 females per treatment.